AIDS e envelhecimento homossexual: representações gerontológicas e a linguagem da patologia - Ferreira, João Paulo (2021)
This thesis sociologically explores the continuities and ruptures of research on homosexuality and aging from 1970 to 2018. Specifically, it inquiries how the biogerontological sciences have represented homosexuality under the analytical perspective “inclusion-difference”. This prism, called the “inclusion-difference paradigm”, was crystallized mainly in the 1990s in research policies involving funding, recruitment and selection of populations for experimental and randomized studies in the United States. That is, when the so-called “special groups” were included in clinical research funded by the National Institute of Health, and sociological categories were reincorporated into the studies in the form of both political and epidemiological imperatives. The results attest, first, that the representations of homosexuality in (bio)gerontology were split by the sexual panic caused by the HIV/AIDS epidemic in the 1980s and 1990s. Secondly, they allow us to visualize how the discourse for “inclusion” was constituted in association with “difference”, not necessarily providing a more positive vocabulary to people socially demarcated as part of “special groups”. In this context, this study also examined the centrality acquired by the language of pathology during the deadliest period of the HIV-AIDS epidemic – 1981 to 2000 –, confirming not only its descriptive but normative configurations. The language of pathology formed during AIDS epidemic, as evidenced by the data, was closely linked to moralizing discourses, even after the commercial availability of Highly Active Antiretroviral Therapy (HAART), in 1996. While “high risk”, “gay men”, “MSM”, “person with AIDS” and “anal” syncretized and responded to the already known frameworks of gender and sexuality produced by the biomedical sciences, other processes of stigmatization followed a historically unknown trend in biogerontology. As part of the research developed at Harvard University, in the United States, and in the analysis of the AIDS’ Obituaries section – from more than five thousand death records collected from the editions of the Bay Area Reporter, from 1982 to 2000 –, the study produced original information that allowed us to know how deaths also increased an epidemiological vocabulary that conceived a “mortality prophylaxis” based on racializing descriptions. In methodological terms, the research was based on qualitative and quantitative documentary analysis, carried out in the Web of Science database and in collections on sexuality, history of science and AIDS from the Arthur and Elizabeth Schlesinger library, from the Radcliffe Institute for Advanced Study, and from the New York Public Library. Empirical evidence shows that there was a kind of “categorical alignment” in relation to biomedical definitions of homosexuality and aging in the context of the inclusion of so-called “special groups” in the 1990s; and the consolidation of a change in the language of pathology since the spread of HIV-AIDS.